Kondisi Optimum Pengaturan Lampu Lalu Lintas Simpang DPRD dan Simpang Presiden Di Kota Padang - Kefiano Fangelis; Defri Ahmad (UNIVERSITAS NEGERI PADANG, 2020)
Abstract — The high traffic density on roads in Padang has resulted in the accumulation of vehicles at intersections, especially the DPRD and the president intersection. Optimal traffic light settings are needed to reduce vehicle buildup at these intersections. Optimization is done by applying a graph coloring application. This optimization is seen from increasing the duration of green lights and decreasing the duration of red lights based on traffic density and road width. This study aims to determine the optimal traffic light settings at the DPRD intersection and the President's intersection of the city of Padang by using Graph Coloring.. This research is applied research,and data used are primary data obtained from direct observation. The completion of traffic light settings using graph coloring provides an alternative solution for the duration of the lights that is more effective than the data obtained from the observations. The results obtained are more optimal based on the level of effectiveness where the duration of the red light for the DPRD intersection and the president's intersection decreased by 9,27% and 39,02%, while the duration of the green light increased by 30,8% and 239,6%.Keywords — Coloring Graph, Weighted graph, Welch-Powell, Traffic Light.